(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
This work aims to compare two languages that are very different in grammar and pronunciation, namely German and Albanian. Since the field of possible investigations in comparative linguistics is endless, the present work concentrates on imperative sentences and their respective lingual forms. In detailed analyzes of sentence examples, which are taken from common German-speaking and Albanian grammars, the differences and similarities regarding imperative sentences are shown. As a regulatory framework serves the distinction in German grammar between sentences of request (‚Aufforderungssätze‘) and strict imperatives (commands). At the end of the work, the knowledge gained is summarized in an overview. Keywords: German; Albanian; comparative analysis; imperatives; imperative sentences.